Wind Erosion Resistance Effect of Conservation Tillage: The Case of Chestnut Soil in Mongolian Plateau - Tong, Xin; Hao, Baoer; Chen, Zhi; Liu, Haiyang (Revista Ciência Agronômica, 2022)
To quantitatively evaluate the effect of stubble height and mulching on soil resistance to wind erosion in protected cultivated chestnut soil farmland under different wind speed conditions, tests were carried out on conservation and conventional tillage in Mongolian Plateau, China, using a mobile wind erosion wind tunnel. Chestnut soils were a soil type in fragile semi-arid ecosystems that were susceptible to desertification following wind erosion and were found mainly in Central Asia and the North American continent. The results show that soil erosion on conservation tillage was lower than conventional tillage at different wind speeds. The resistance of conservation tillage to soil wind erosion increases with increasing stubble height and cover. At a stubble height of 300 mm and 50% cover, conservation tillage's average wind erosion resistance efficiency was 74.82%, effectively preventing wind erosion of agricultural soils.